Surgical management of the bilateral maxillary buccal exostosis - Shalu Chandna; Surinder Sachdeva; Deepak Kochar; Harsh Kapil (Wolters Kluwer Medknow Publications, 2015)
Buccal exostosis is benign, broad-based surface masses of the outer or facial aspect of the maxilla and less commonly, the mandible. They begin to develop in early adulthood and may very slowly enlarge over the years. A 24-year-old female presented with gingival enlargement on the buccal aspect of both the quadrants of the maxillary arch. The overgrowth was a cosmetic problem for the patient. The etiology of the overgrowth remains unclear though the provisional diagnosis indicates toward a bony enlargement, which was confirmed with the help of transgingival probing. The bony enlargement was treated with resective osseous surgery. The following paper presents a rare case of the bilateral maxillary buccal exostosis and its successful management.